Length-weight relationships of the Indian Major Carp, Labeo rohita (Cypriniformes: Cyprinidae) from six drainages of Ganga basin, India (UNED Research Journal, 2015)
The Indian Major Carp, Labeo rohita, is a geographically widespread and economically important food fish species in tropical freshwater of India and adjacent countries. We studied the lengthweightrelationships of 1 033 specimens collected from the main channel of Ganga river and its five major drainages from March 2009 to July 2012. The length of males ranged from 16 to 92cm (females: 16to 94cm). The growth is allometric positive (b>3) for males, females and pooled sexes. The coefficient of determination (r2) in males ranged from 0,978 to 0,989 and for females from 0,958 to 0,985. Data from field populations are scarce and our results will be useful in the management and conservation of L. rohita populations in its natural range.
Keywords: LWR; Ganga basin; growth; wild; India.